DOP87 The Anti-TL1A Antibody PRA023 Demonstrated Proof-of-Concept in Crohn's Disease: Phase 2a APOLLO-CD Study Results. (30th January 2023) - Feagan, B G; Sands, B; Siegel, C A; Dubinsky, M; Longman, R; Sabinho, J; Laurent, O; Luo, A; Lu, J D; Nguyen, D; Towfic, F; DuVall, A; et al.
Abstract: Background: Tumor necrosis factor-like cytokine 1A (TL1A) is an upstream regulator of pro-inflammatory cytokines and fibrosis signals. PRA023 is an anti-TL1A monoclonal antibody in development for multiple inflammatory/fibrotic diseases with a precision medicine approach. This Phase 2a multi-center, open-label study aimed to assess the efficacy and safety of PRA023 as induction treatment in adults with moderately to severely active Crohn's Disease (CD). Methods: Key eligibility criteria included Crohn's disease activity index ≥220 and ≤450 with centrally read [with adjudication] Simple Endoscopic Score (SES)-CD score of ≥6 (≥4 isolated ileal disease) and a history of insufficient/loss of response and/or intolerance to conventional and/or approved biologic therapies (≤4 biologic agents from ≤3 classes). Eligible patients were treated with intravenous PRA023 1000mg on Day 1, 500mg at Weeks 2, 6, and 10. The primary endpoint was endoscopic response (reduction in SES-CD score of ≥50%) at Week 12. Study design utilized historical placebo control rate estimates as a benchmark. Exploratory endpoints include efficacy assessment in a subpopulation identified by a genetics-based companion diagnostic test (CDx). Results: Of the 55 patients in the full analysis data set, 53 (96.4%) completed the 12-week Induction Period. The patient population was notable for the high rate of prior biologic exposure (70.9%) and a mean (SD) disease duration of 10.3 (9.3) years (Table 1). A significantly greater proportion of patients receiving PRA023 achieved endoscopic response (26% PRA023 vs. 12% historical placebo estimate, p=0.002) and clinical remission (CDAI < 150 points; 49% PRA023 vs 16% historical placebo estimate, p< 0.001). Efficacy was observed in biologic-exposed patients (33% endoscopic response and 38.5% clinical remission) while concurrent steroid or immunosuppressant use did not impact efficacy. Significant reductions from baseline in C-reactive protein and fecal calprotectin were observed at all timepoints (Figure 1). Although the pre-specified CDx algorithm provided only limited additional benefit in clinical responses, an alternative CD-specific algorithm (not based on clinical trial data) using the same genetic markers demonstrated enhanced performance across both clinical (12/21 [57%] remission) and endoscopic (9/20 [45%] response) outcomes. No serious/severe AEs were deemed as study drug-related. Conclusion: This Phase 2a study demonstrated robust proof-of-concept for PRA023's efficacy in moderately to severely active CD with favorable tolerability. Patient selection using prespecified genetic markers showed promising results. Placebo-controlled clinical trials will be conducted to confirm these findings.